Human epidermal growth factor receptor 2 status of breast cancer patients in Asia: Results from a large, multicountry study. Issue 4 (23rd June 2016) - Pathmanathan, Nirmala; Geng, Jing‐shu; Li, Wencai; Nie, Xiu; Veloso, Januario; Hill, Julie; McCloud, Philip; Bilous, Michael
Abstract: Aim: Current estimates of the human epidermal growth factor receptor 2 (HER2)‐positivity rate in breast cancer are largely based on studies from the United States, Europe and Australia, and might not reflect the rate among breast cancer patients in Asia. The primary aim of this study was to conduct a clinical audit of laboratories across eight countries in Asia to determine the incidence of HER2‐positive breast cancer in this region. Methods: Pathology laboratories submitted data on breast cancers consecutively tested for HER2 over a two‐year period. The proportion of HER2‐positive, ‐equivocal and ‐negative tumors was determined for each country and overall. HER2‐positivity rate by age and histological grade was also determined. Results: HER2 results from 30 179 breast cancers were submitted by 96 laboratories. The overall HER2‐positivity rate was 23.5%; the rate between countries ranged from 19.7% to 44.2%, and from 4.4% to 51.6% between laboratories. An equivocal HER2 result was recorded in 18.2% of cases. Discrepancies between laboratories suggest that testing expertise contributes to variations seen in HER2 status across laboratories, as well as the generally higher rate of HER2‐positivity that was recorded. Conclusion: In this study, the incidence of HER2‐positive breast cancer diagnosed in Asian women was higher than published studies on women from Western countries. In addition, the study found that women in Asian countries presented with breast cancer at an earlier age, with a higher histological grade. This study serves to highlight the challenges with HER2 testing and data collection in a large multicenter Asian cohort.